Determinants of the development of foreign economic activity in Hungary - Nagy, Szabolcs; Pererva, P. G. (Луцький національний технічний університет, 2022)
The analysis of innovative development, the forecast of export-import flows and the identification of key factors for increasing the export potential of Hungary were carried out. The research hypothesis is that the key factors in the innovative development of Hungary's export potential are smart investments in the transport and logistics system, human capital in the medium and high-tech sector, the vector of the high-tech service sector, investments in science, research, e-commerce.
Детермінанти розвитку зовнішньоекономічної діяльності в Угорщині
Keywords: foreign economic activity; determinants of development; integration; European Union; Hungary